1997
DOI: 10.1136/tc.6.4.285
|View full text |Cite
|
Sign up to set email alerts
|

Smoking experimentation and initiation among adolescent girls: qualitative and quantitative findings

Abstract: Smoking prevention and cessation programmes need to address and counter the smoking/relaxation association, which was identified as an important reason for smoking among adolescent girls. Questions typically used in surveys to measure smoking behaviour do not adequately define the smoking experience as described by teenagers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
80
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(89 citation statements)
references
References 17 publications
8
80
1
Order By: Relevance
“…Our findings indicate that most people did not experience classical peer pressure when they first took ecstasy, but that Ecstasy-using friends did play a major or minor role in their decision to take the drug. Normative influence thus appears to be more significant here than direct or overt influence, which is in accordance with qualitative literature about smoking initiation (Nichter, Nichter, Vuckovic, Quintero, and Ritenbaugh, 1997;Stewart-Knox et al, 2005). Peer selection seems very uncommon at the stage of initiation.…”
Section: Conclusion and Discussionsupporting
confidence: 81%
“…Our findings indicate that most people did not experience classical peer pressure when they first took ecstasy, but that Ecstasy-using friends did play a major or minor role in their decision to take the drug. Normative influence thus appears to be more significant here than direct or overt influence, which is in accordance with qualitative literature about smoking initiation (Nichter, Nichter, Vuckovic, Quintero, and Ritenbaugh, 1997;Stewart-Knox et al, 2005). Peer selection seems very uncommon at the stage of initiation.…”
Section: Conclusion and Discussionsupporting
confidence: 81%
“…The importance attributed to relaxation motives is echoed in findings by Dozois et al (1995) and Nichter, Nichter, Vuckovic, Quintero, and Ritenbaugh (1997), who similarly found that smoking to relax and stress reduction were commonly reported motives among adolescent smoking initiates. Recent studies by Johnson et al (2003Johnson et al ( , 2005) also point to the significant endorsement of emotional reinforcement motives, as a large proportion of adolescent smokers attributed their smoking to its ability to facilitate affect regulation.…”
Section: Do Adolescents Smoke To Regulate Affect?mentioning
confidence: 95%
“…Nichter and others [8] argue that teenagers feel that they should smoke if others around them smoke. Youths smoke to be socially acceptable, "fit in," and to facilitate social interaction [9].…”
mentioning
confidence: 98%